Kontrol Diri dalam Perilaku Merokok pada Remaja Laki-Laki - Abdillah, Abdillah; suarni, waode; Kaimuddin, Sitti Mikarna (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Adolescence is a time when an individual is looking for identity. In searching for identity, sometimes a teenager does things that shouldn't be like smoking behavior. Smoking behavior is the activity of burning cigarettes made of tobacco and wrapped in paper and then inhaling the smoke and then exhaling it out of the body. Smoking behavior is a form of juvenile delinquency related to self-control abilities. Self-control or self-control is an important factor in controlling and directing adolescent behavior. Adolescents who have high self-control will be able to control and direct their behavior. The teenager is generally still able to control the impulses that exist in him. This study aims to determine whether self-control plays a role in smoking behavior in male adolescents at SMKN 2 Kendari. This type of research is quantitative with an ex-post facto research design. The population in this study were 613 students. The sample of this research was 89 people who were taken using a purposive sampling technique with the criteria of male students, class X and XI, and students who smoked. The research instrument used a self-control scale and smoking behavior scale. Data analysis technique using simple regression analysis. The results showed that self-control played a role in smoking behavior with a significance value of 0.001 (P